Applying Shainins Tools to Process Improvement for Reducing Cracking Defect of Sanitary Product - Tossapol Kiatcharoenpol; Rachan Seeluang; Sakon Klongboonjit (My University, 2023)
The objective of this research attempt is to implement the DMAIC (Define, Measure, Analyze, Improve, Control) approach, a part of the Six Sigma methodology, in order to diminish the loss of sanitary ware during the production process. Specifically, this study focuses on addressing the issue of cracking defects that often occur in the production of sanitary wares after the firing process. Cracking defects manifest as gaps on the surface of sanitary wares, resulting in nonconforming and aesthetically inferior products. The AG27 Model, a highly demand toilet bowl, was selected as the case study due to its significant occurrence of cracking defects, accounting for 20% of the total defective units. The research utilizes the Six Sigma methodology in conjunction with Shainin's tools to identify the root causes and enhance production yield. The employed Shainin's tools include the Family of variation (FOV's), Concentration chart, Paired comparison, and Better and current (B vs C). The primary focus area of investigation involves the variation in the forming process and the design of the plaster mold. Through the use of the concentration chart, it was determined that the cracking defects predominantly appear along the border line between the rim and body of the toilet bowl. Subsequent experiments, based on paired comparison, confirmed that the design of the border line, which incorporates a hollow body shape, and the potential degradation of mold quality due to frequent use, were the two significant factors contributing to the cracking defects. In order to address these issues, a new design was implemented to enhance the connection between the rim and solid body of the AG27 toilet bowl. The practicality of this solution was validated through the utilization of the B vs C tool during the improvement phase. As a result, the occurrence of cracking defects decreased from approximately 4.0% to 1.92% during the control phase, representing a potential reduction of defects by over 50%.
Keywords: DMAIC; Production line; Toilet; Manufacturing Process and Optimization